2012
DOI: 10.1016/j.brainresbull.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The elevated T-maze task as an animal model to simultaneously investigate the effects of drugs on long-term memory and anxiety in mice

Abstract: The elevated T-maze (ETM) is an apparatus derived from the elevated plus-maze test, which is used to evaluate anxiety. Because anxiety is a biasing factor in models of memory, this study proposed the ETM as a task for the simultaneous assessment of memory and anxiety in mice. The ETM consists of one enclosed and two open arms. The procedure is based on the avoidance of open spaces learned during training session, in which mice were exposed to the enclosed arm as many times as needed to stay 300s. In the test s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Due to possible misinterpretations, the available animal models for learning and memory seem to have a limited ability to detect the effect of drugs on fear and anxiety. Therefore, the proposed test-retest paradigm in the elevated plus-maze (EPM) task is an attempt to concomitantly assess the effects of drugs on anxiety, learning and memory in rodents [6]. The use of EPM in testing anxiety is based on the natural tendency of animals to avoid dangerous situations when they face height and open spaces [91].…”
Section: Introductionmentioning
confidence: 99%
“…Due to possible misinterpretations, the available animal models for learning and memory seem to have a limited ability to detect the effect of drugs on fear and anxiety. Therefore, the proposed test-retest paradigm in the elevated plus-maze (EPM) task is an attempt to concomitantly assess the effects of drugs on anxiety, learning and memory in rodents [6]. The use of EPM in testing anxiety is based on the natural tendency of animals to avoid dangerous situations when they face height and open spaces [91].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental protocol was based on the reports of Asth et al (2012). The ETM was made of wood and had three arms of equal dimensions (30×6 cm).…”
Section: Elevated T-maze Taskmentioning
confidence: 99%
“…Aside from the limited number of studies, some reports employed the ETM task as an animal model of memory in rats (Santos et al 2006;Cruz-Morales et al 2008;do Maia et al 2010) and mice (Takahashi et al 2005;Asth et al 2012). Despite differences in protocols used, it has been observed that exposure to stress, striatal serotonin modulation (CruzMorales et al 2008), exposure to ethanol and methylmercury in rats during central nervous system development (do Maia et al 2010), and microinjections of antagonist 7-chlorokynurenic acid (Santos et al 2006) impair aversive memory in the rat ETM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations